KONSEP TEOLOGI DALAM TEKS JNANA SIDDHANTA - Ni Made Evi Kurnia Dewi (Jnanasidanta, 2020)
The religion and cultural traditions of Hindus in Bali cannot be separated from each other. Lontar is a written media which is used in the earlier period before the discovery of the paper as a part of the renewable technology. Tatwa Jnana is a lontar which teaches about the teachings of Sang Hyang Tatwa Jnana and Sang Hyang Prayogasandhi. Tatwa Jnana means the science of truth or the knowledge of the highest nature which is the basis of all tattwa (bungkahing tattwa kabeh) which describes the teachings of the divine (tattwa). This Lontar Tattwa jnana places Bhatara Siwa (Siwatattwa) as the highest causal in every worship. The concept of divine teachings contained is the concept of Nirguna Brahman, the transcendent concept of God without beginning or end, cannot be imagined as anything, in this concept God cannot be recognized as anything, because Brahman is not this or that (neti neti) and the concept of Saguna Brahman is the concept of God that is Immanent, can be described, conceivably has attributes as symbols.